Peran Dukungan Keluarga, Modal Finansial dan Ketrampilan Manajerial dalam Meningkatkan Minat Berwirausaha Mahasiswa Fakultas Ekonomi Undiksha - Ni Komang Yuli Sari Ningsih; Made Ary Meitriana (Fakultas Ekonomi Universitas Pendidikan Ganesha, 2026)
This research is motivated by the low level of entrepreneurial interest among students despite the increasing availability of business opportunities. This study aims to analyze the role of family support, financial capital, and managerial skills in increasing entrepreneurial interest among students at the Faculty of Economics, Ganesha University of Education. This study uses a qualitative approach with a descriptive research type. Data collection techniques were carried out through interviews, observation, and documentation with students as the main informants. Data analysis was carried out through the stages of data reduction, data presentation, and conclusion drawing. The results of the study indicate that family support plays a role in providing motivation, self-confidence, and moral support for students to become entrepreneurs. Financial capital helps students in starting and developing businesses, although limited capital does not completely hinder entrepreneurial interest. Managerial skills support students' ability to manage businesses more effectively. Based on the results of the study, it can be concluded that family support, financial capital, and managerial skills have an important role in increasing entrepreneurial interest among students at the Faculty of Economics, Ganesha University of Education.